The comoving infrared luminosity density: Domination of cold galaxies across 0 < z < 1 - Seymour, Nick; Symeonidis, M.; Page, M.; Huynh, M.; Dwelly, T.; McHardy, I.; Rieke, G. (Oxford University Press, 2010)
In this paper, we examine the contribution of galaxies with different infrared (IR) spectral energy distributions (SEDs) to the comoving IR luminosity density (IRLD), a proxy for the comoving star formation rate (SFR) density. We characterize galaxies as having either a cold or hot IR SED depending on whether the rest-frame wavelength of their peak IR energy output is above or below 90 µm. Our work is based on a far-IR selected sample both in the local Universe and at high redshift, the former consisting of IRAS60 µm-selected galaxies at z < 0.07 and the latter of Spitzer70 µm selected galaxies across0.1 < z= 1. We find that the total IR luminosity densities for each redshift/luminosity bin agree well with results derived from other deep mid-/far-IR surveys. Atz < 0.07, we observe the previously known results that moderate luminosity galaxies(LIR < 1011 L?) dominate the total luminosity density and that the fraction of cold galaxies decreases with increasing luminosity, becoming negligible at the highest luminosities. Conversely, abovez= 0.1, we find that luminous IR galaxies(LIR > 1011 L?), the majority of which are cold, dominate the IRLD. We therefore infer that cold galaxies dominate the IRLD across the whole0 < z < 1 range, hence appear to be the main driver behind the increase in SFR density up toz~ 1 whereas local luminous galaxies are not, on the whole, representative of the high-redshift population. © 2010 The Authors. Journal compilation © 2010 RAS.